Liquid Crystals: Planar Anchoring of C70 Liquid Crystals Using a Covalent Organic Framework Template (Small 45/2019). Issue 45 (6th November 2019) - Cui, Daling; MacLeod, Jennifer M.; Rosei, Federico
Abstract : In article number 1903294, Daling Cui, Jennifer M. MacLeod, and Federico Rosei anchor the growth of liquid crystals with molecular building units (ellipsoid C70 molecules) using a defined nanometer‐scale template (monolayer covalent organic frameworks). Using a surface‐confined template to anchor the initial layer of liquid crystal molecules could be a modular and potentially broadly applicable approach for organizing molecular mesogens into liquid crystals.